Multistage Approximate Analytical Solution Of Non-Autonomous Nonlinear Ordinary Differential Systems - Khalil, Al Ahmad (2020)
Differential equations are an important tool for modeling many problems in sci- ence, chemistry, physics and economics. Differential equations system can be divided into two kinds: autonomous and non-autonomous system. The objective of this re- search is to develop a technique for solving non-autonomous nonlinear differential sys- tems which is based on the standard Differential Transform Method (DTM) and Mul- tistage Differential Transform method (MsDTM). A comparative analysis between the solutions that were obtained by the proposed methods and Runge-Kutta method will also be discussed